Cytokine gene transcription in the trachea, Harderian gland, and trigeminal ganglia of chickens inoculated with virulent infectious laryngotracheitis virus (ILTV) strain. Issue 5 (3rd September 2018) - Vagnozzi, Ariel Eduardo; Beltrán, Gabriela; Zavala, Guillermo; Read, Leah; Sharif, Shayan; García, Maricarmen
ABSTRACT: The objective of this study was to determine how cytokine transcription profiles correlate with patterns of infectious laryngotracheitis virus (ILTV) replication in the trachea, Harderian gland, and trigeminal ganglia during the early and late stages of infection after intratracheal inoculation. Viral genomes and transcripts were detected in the trachea and Harderian gland but not in trigeminal ganglia. The onset of viral replication in the trachea was detected at day one post-infection and peaked by day three post-infection. The peak of pro-inflammatory (CXCLi2, IL-1 β, IFN- γ ) and anti-inflammatory (IL-13, IL-10) cytokine gene transcription, 5 days post-infection, coincided with the increased recruitment of inflammatory cells, extensive tissue damage, and limiting of virus replication in the trachea. In contrast, transcription of the IFN- β gene in the trachea remained unaffected suggesting that ILTV infection blocks type I interferon responses. In the Harderian gland, the most evident transcription change was the early and transient upregulation of the IFN- γ gene at 1 day post-infection, which suggests that the Harderian gland is prepared to rapidly respond to ILTV infection. Overall, results from this study suggest that regulation of Th1 effector cells and macrophage activity by Th1/2 cytokines was pertinent to maintain a balanced immune response capable of providing an adequate Th1-mediated protective immunity, while sustaining some immune homeostasis in preparation for the regeneration of the tracheal mucosa.